Cytotoxic T-Lymphocyte-Associated Protein-4 and Lymphocyte Activation Gene-3 Expression in Orbitally-Invasive Versus Nodular Basal Cell Carcinoma. (May 2021) - Lajoie, Juliann E.; Lau, Kevin W.; Adam, Alejandro P.; Wladis, Edward J.
Abstract : Purpose: To compare the expression of cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) and lymphocyte activation gene-3 (LAG-3) in nodular and orbitally-invasive forms of basal cell carcinoma (BCC). Methods: Immunohistochemical staining for CTLA-4 and LAG-3 was performed on the pathology specimens of BCC from orbital exenteration and nodular forms. The numbers of positively-staining cells/×40 field were counted across 5 consecutive fields of each specimen and statistical analysis was performed to calculate the difference in expression between the 2 groups. Results: Nine cases of orbitally-invasive BCC and 6 cases of nodular BCC were studied. The mean numbers of CTLA-4-positively staining cells were 11.51 cells/×40 field (median = 6.60 cells/×40 field, range = 0.4–31.8 cells/×40 field) in invasive BCC and 0.90 cells/×40 field (median = 0.60 cells/×40 field, range = 0.0–2.8 cells/×40 field) in nodular specimens. The difference between the 2 groups was statistically significant ( p = 0.0030). The mean number of LAG-3-positively staining cells was 0.58 cells/×40 field (median = 0.0, range = 0.0–2.8 cells/×40 field) in invasive BCC and 3.13 cells/×40 field (median = 0.0, range = 0.0–18.18 cells/×40 field). There was no significant difference in LAG-3 positivity between tumor groups ( p = 0.5564). Conclusions: CTLA-4 expression was enriched in orbitally invasive BCC compared with nodular forms of BCC, whereas LAG-3 expression did not differ between these entities. CTLA-4 mediated immune suppression may facilitate the development of orbitally invasive BCC. Treatment strategies that use existing medications to target CTLA-4 may decrease the requirement for orbital exenteration and provide enhanced survival outcomes. Abstract : CTLA-4 is enriched in orbitally invasive basal cell carcinoma.